Calibration of silicone rubber rods as passive samplers for pesticides at two different flow velocities: Modeling of sampling rates under water boundary layer and polymer control. (8th February 2018) - Martin, Alexis; Margoum, Christelle; Jolivet, Antoine; Assoumani, Azziz; El Moujahid, Bachir; Randon, Jérôme; Coquery, Marina
Abstract: There is a need to determine time‐weighted average concentrations of polar contaminants such as pesticides by passive sampling in environmental waters. Calibration data for silicone rubber‐based passive samplers are lacking for this class of compounds. The calibration data, sampling rate ( R s ), and partition coefficient between silicone rubber and water ( K sw ) were precisely determined for 23 pesticides and 13 candidate performance reference compounds (PRCs) in a laboratory calibration system over 14 d for 2 water flow velocities, 5 and 20 cm s −1 . The results showed that an in situ exposure duration of 7 d left a silicone rubber rod passive sampler configuration in the linear or curvilinear uptake period for 19 of the pesticides studied. A change in the transport mechanism from polymer control to water boundary layer control was observed for pesticides with a log K sw of approximately 3.3. The PRC candidates were not fully relevant to correct the impact of water flow velocity on R s . We therefore propose an alternative method based on an overall resistance to mass transfer model to adjust R s from laboratory experiments to in situ hydrodynamic conditions. We estimated diffusion coefficients ( D s ) and thickness of water boundary layer (δw ) as adjustable model parameters. Log Ds values ranged from −12.13 to −10.07 m 2 s −1 . The estimated δw value showed a power function correlation with water flow velocity. Environ Toxicol Chem 2018;37:1208–1218. © 2017 SETAC